Amalan pengurusan Guru Besar dan motivasi kerja guru di sekolah rendah - Rohani, Md. Adam (2012)
The study of descriptive using the colerative method aims to undermine the highest dominance in the administration level of the headmaster and motivation work levels of the teachers in primary schools. The study also aims to see the difference of motivation in work based on the teachers gender, teaching experience and age in the primary school. The respondence of the study consists of 123 teachers from seven primary schools in Jementah Zone in Segamat District. The questionaire given consists of three sections with the aim of obtaining information of the respondence background, the administration level of headmaster and the motivation work level of the teachers. The study instrument was tested based on Alpha Cronbach scale within 20 teachers from a primary school in Jementah Zone, Segamat District to determine the trustworthy of it.The results of this study shows a high level of trustworthiness which is (0.934) administrative of headmasters, and (0.899) at level of work motivation of teachers. The data of the study was analized using the, Statistical Package For The School Science (SPSS) Version 17.0 to obtain the min, percentage, t-test, ANOVA and Spearman rho coleration. The results from the study shows the administration level of headmasters are high and so is the motivation work levels of the teachers. The hypothesis study shows no significant difference in motivation based on teachers gender, teaching experience and their age. Through the relationship analysis, it shows that a significant connection between the level of headmaster’s administration and the work motivation level of teachers. Finally a few suggestions have been suggested to further the study of this research in future.